Termografia infravermelha dos músculos da mastigação em pacientes com disfunção temporomandibular muscular e queixa otológica - Feitosa, Luciana Cerqueira [UNIFESP] (2019)
Introduction: Temporomandibular dysfunction (TMD) is defined by the American Academy of Orofacial Pain (AAOP) as a collective term, comprising a series of clinical problems involving the masticatory muscles and temporomandibular joint (TMJ). Some otological symptoms such as tinnitus, a feeling of fullness or congestion in the ears, and dizziness are frequently reported by TMD patients, and this connection may be the result of chewing muscle hyperactivity. The aim of this study was to evaluate by Infrared Thermography the anterior masseter and temporalis muscles in TMD and tinnitus patients. Method: The sample consisted of 130 female volunteers between 18 and 70 years old and was divided into 4 distinct groups. Results: The results showed that patients with muscular TMD had lower temperatures in the anterior temporal and masseter muscle region and with an asymmetrical pattern in the thermograms analyzed. The thermographic exam can be used in addition to the physical exam of the TMJ and was considered an efficient tool for the diagnosis of TMD, as it recorded the changes in the skin surface temperature in the pain areas and because it was not an invasive, painless and painful examination. Easy execution. Conclusion: The complaint of tinnitus was significantly related to TMD.